A combination of red structural and pigmentary coloration in the eyespot of a copepod. Issue 190 (25th May 2022) - Justyn, Nicholas M.; Heine, Kyle B.; Hood, Wendy R.; Peteya, Jennifer A.; Vanthournout, Bram; Debruyn, Gerben; Shawkey, Matthew D.; Weaver, Ryan J.; Hill, Geoffrey E.
Abstract : While the specific mechanisms of colour production in biological systems are diverse, the mechanics of colour production are straightforward and universal. Colour is produced through the selective absorption of light by pigments, the scattering of light by nanostructures or a combination of both. When Tigriopus californicus copepods were fed a carotenoid-limited diet of yeast, their orange-red body coloration became faint, but their eyespots remained unexpectedly bright red. Raman spectroscopy indicated a clear signature of the red carotenoid pigment astaxanthin in eyespots; however, refractive index matching experiments showed that eyespot colour disappeared when placed in ethyl cinnamate, suggesting a structural origin for the red coloration. We used transmission electron microscopy to identify consecutive nanolayers of spherical air pockets that, when modelled as a single thin film layer, possess the correct periodicity to coherently scatter red light. We then performed microspectrophotometry to quantify eyespot coloration and confirmed a distinct colour difference between the eyespot and the body. The observed spectral reflectance from the eyespot matched the reflectance predicted from our models when considering the additional absorption by astaxanthin. Together, this evidence suggests the persistence of red eyespots in copepods is the result of a combination of structural and pigmentary coloration.